Brain functional impairment in beta‐thalassaemia: the cognitive profile in Italian neurologically asymptomatic adult patients in comparison to the reported literature. (20th May 2019) - Tartaglione, Immacolata; Manara, Renzo; Caiazza, Martina; Carafa, Pasquale Alessandro; Caserta, Violetta; Ferrantino, Teresa; Granato, Ilaria; Ippolito, Noemi; Maietta, Caterina; Oliveto, Tiziana; Casale, Maddalena; Di Concilio, Rosanna; et al.
Summary: Cognitive involvement in beta‐thalassaemia is strikingly controversial and poorly studied in adulthood. This multicentre prospective study investigated 74 adult neurologically‐asymptomatic beta‐thalassaemia patients (mean‐age 34·5 ± 10·3 years; 53 transfusion‐dependent [TDT], 21 non‐transfusion dependent [NTDT]) and 45 healthy volunteers (mean‐age 33·9 ± 10·7 years). Participants underwent testing with Wechsler Adult Intelligence Scale‐Fourth Edition (WAIS‐IV), Brief Psychiatric Rating Scale (BPRS) and multiparametric brain 3T‐magnetic resonance imaging (MRI) for parenchymal, vascular and iron content evaluation. Patients had lower Full‐Scale Intelligence Quotient (FSIQ) than controls (75·5 ± 17·9 vs. 97·4 ± 18·1, P < 0·0001) even after correction for education level. Compared to TDT, NTDT showed a trend of higher FSIQ ( P = 0·08) but a similar cognitive profile at WAIS‐subtests. FSIQ correlated with total and indirect bilirubin ( P < 0·0001 and P = 0·002, respectively); no correlation was found with splenectomy, intracranial MRI/magnetic resonance‐angiography findings, brain tissue iron content or other disease‐related clinical/laboratory/treatment data. FSIQ did not correlate with BPRS scores, although the latter were higher among patients (28·74 ± 3·1 vs. 27·29 ± 4·8, P = 0·01) mainly because of increased depression and anxiety levels. Occupation rate was higher among controls (84·4% vs. 64·9%, P = 0·004) and correlated with higher FSIQ ( P = 0·001) and education level ( P = 0·001). In conclusion, Italian adult beta‐thalassaemia patients seem to present a characteristic cognitive profile impairment and an increased rate of psychological disorders with possible profound long‐term socio‐economic consequences.